Impact of Farm Mechanization on Selected Filed Crops in Tamil Nadu (India): An Analysis - N. Anandaraja; K. Chandrakandan; R. Vijayaraghavan; C. Karthikeyan (Journal of Agricultural Extension Management, 2025)
The economic progress of the nation is directly expressed by the overall availability of energy and its consumption. Increase of input in agriculture directly or indirectly increases the production and productivity. In the age-old system of agriculture, the draught animal was the predominant motive power source for operations such as tillage, post-harvest and haulage etc. it is an established fact that inadequacy of the power and machinery results in very poor yields. Therefore, in order to bring more land under cultivation and to improve productivity, it is imperative to introduce other sources of power on the farm